A nationwide population-based cross-sectional time series study of hospitalized chronic liver disease burden in Thailand from 2017 to 2022 - Rungfah Saehan; Apichat Kaewdech; Pimsiri Sripongpun; Naichaya Chamroonkul; Teerha Piratvisuth; Suthat Liangpunsakul; Ponlagrit Kumwichar (Scientific Reports)
Abstract Chronic liver disease (CLD) is a major global public health challenge due to its high morbidity and mortality. In Thailand, the burden of CLD remains underexplored despite its significant impact on healthcare systems. This study examines trends in hospitalizations, etiologies, and in-hospital mortality associated with CLD, including cirrhosis and hepatocellular carcinoma (HCC), from 2017 to 2022. We conducted a nationwide, population-based, cross-sectional time-series study using inpatient claims data from the National Health Security Office (NHSO) in Thailand. Data from fiscal years 2016 to 2022 were analyzed, focusing on CLD-related hospitalizations categorized by etiology using ICD-10 codes. Age- and sex-standardized incidence and mortality rates were assessed through descriptive and trend analyses, with LOESS smoothing applied to identify temporal patterns. Between 2017 and 2022, 119,464 hospitalizations for CLD were recorded, with 77% of patients being male and a median age of 45–66 years. Alcohol-associated liver disease was the leading cause (30.8%), followed by chronic hepatitis B (11.3%), hepatitis C (10.3%), and metabolic dysfunction-associated steatotic liver disease (MASLD, 9.6%). Etiology was unidentified in 37.5% of cases. Cirrhosis accounted for most hospitalizations, with a stable incidence of 1200–1600 cases per month. Alcohol-associated cirrhosis was the most prevalent, while MASLD-related cirrhosis had the highest mortality. Age-standardized mortality rates for hepatitis B- and C-related cirrhosis declined over the study period. HCC incidence remained stable, with hepatitis B, hepatitis C, and MASLD contributing 23, 16, and 8 cases per 10 million population per month, respectively. By 2022, MASLD-related HCC mortality had surpassed alcohol-related causes. CLD remains a major health burden in Thailand, with high mortality driven by viral hepatitis, alcohol consumption, and MASLD. Strengthening prevention strategies, early diagnosis, and equitable access to effective therapies is essential. Enhanced public health interventions and ongoing surveillance are critical to mitigating the growing CLD burden.